The Cohabitation Snare of the Criminal Code Law: Legal Culture Perspective of Individualism and Social Mechanic Solidarity in Legal Sociology - Putu Pipit Pricellia Eka Putri (Dinasti Research, 2024)
This research aims to analyze the emergence of the cohabitation article from the perspective of legal sociology. The research method used is an empirical juridical type. The data used are primary and secondary data. Data collection techniques were carried out by interviewing 3 (three) respondents from teenagers and parents, as well as library study techniques from relevant books and journals. Data processing is presented using qualitative descriptive techniques. The research results show that the cohabitation article was born from the legal culture of modern social values, one of which is individualism embraced by society, so this encourages the legal behavior of law makers to make legal changes by criminalizing cohabitation. From Durkheim's theory of mechanical solidarity, cohabitation becomes criminalization because there are groups of people who have collective similarities who feel that cohabitation is important to be criminalized.